Positive electrode of zinc-iodine battery, preparation method of positive electrode and battery
By using polyaniline with a specific structure as the positive electrode active material of zinc-iodine batteries, the problems of low efficiency and low specific capacity of zinc-iodine batteries are solved, and higher energy efficiency and battery life are achieved.
Patent Information
- Application Number
- CN202510118938.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-05-06
AI Technical Summary
The existing zinc-iodine battery has low efficiency and low specific capacity, resulting in poor energy efficiency and shortened battery life.
Polyaniline with a specific structure is used as the positive electrode active material, iodine and polyiodine ions are bound by electrostatic action, and a large space between the polyaniline molecular chains with amorphous structure or low crystalline structure is used to block the diffusion of polyiodine ions.
The concentration of iodine ions in the electrolyte is increased, the specific capacity of the material is increased, and the efficiency of the Coulomb is significantly improved, and the life of the battery is extended.
Smart Images

Figure CN119943839A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of batteries, and in particular to a positive electrode of a zinc-iodine battery and a preparation method thereof and a battery. Background Art
[0002] Zinc-iodine battery is a secondary battery with zinc as the negative electrode and iodide as the positive electrode active material. Since the theoretical specific capacities of the positive and negative electrode materials iodine and zinc reach 211mAh / g and 825mAh / g respectively, and the operating voltage can reach about 1.3V, the theoretical energy density of the system can reach 200Wh / kg. Such energy density is relatively prominent in electrochemical energy storage devices using aqueous electrolytes. Moreover, in aqueous electrolytes, zinc-iodine batteries are not prone to combustion or explosion under extreme conditions such as overcharge, overdischarge or short circuit, and have high safety. The biological and environmental toxicity of the positive and negative electrode materials and the electrolyte are low, and they are easy to recycle and are not prone to causing safety problems such as human poisoning or environmental pollution. At present, zinc-iodine batteries mostly use multi-carbon-based porous materials as carriers to fix iodine on the positive electrode. In the presence of I - When present, elemental iodine (I 2 ) will be with I - Combine to form polyiodide ions I which are highly soluble in water (2x+1) - (x≥1), thus causing the iodine ions to leak into the electrolyte. Moreover, since the charge of poly-iodide ions is relatively low, the electric field has a weak binding effect on such poly-iodide ions, which also exacerbates the loss of iodine from the positive electrode. This iodine loss will cause the coulombic efficiency of the battery to be low, affecting its overall energy efficiency, while also shortening the life of the battery. In addition, since the carbon current collector has a weak ability to bind iodine, the mass proportion of the porous carbon carrier in the electrode is high and the mass proportion of iodine is low, making the overall specific capacity of the positive electrode of the zinc-iodine battery not high.
[0003] The prior art discloses an aqueous zinc-iodine secondary battery positive electrode material and a positive electrode thereof and an aqueous zinc-iodine secondary battery, wherein a composite material of ion exchange fiber / resin and iodine is used as a positive electrode active material. Although this technology improves the rate performance and cycle life stability of the aqueous zinc-iodine battery, the resulting battery has low coulombic efficiency and poor energy efficiency. Summary of the invention
[0004] Therefore, the technical problem to be solved by the present invention is to overcome the defect of poor coulombic efficiency performance of zinc-iodine batteries in the prior art, thereby providing a positive electrode of a zinc-iodine battery and a preparation method thereof and a battery.
[0005] Another technical problem to be solved by the present invention is to overcome the defect of low specific capacity of zinc-iodine batteries in the prior art, thereby providing a positive electrode of a zinc-iodine battery and a preparation method thereof and a battery.
[0006] In one aspect, the present invention provides a positive electrode for a zinc-iodine battery, the positive electrode comprising a current collector, a positive electrode active material layer disposed on the current collector,
[0007] The positive electrode active material layer includes polyaniline,
[0008] The polyaniline has a structure shown in formula (I),
[0009]
[0010] In formula (I), n≥20.
[0011] It should be noted that the degree of polymerization in polyaniline has nothing to do with the ability to bind polyiodide ions in the present invention. Therefore, the embodiments of the present invention do not limit the polymer in polyaniline.
[0012] Preferably, in formula (I), the value of n ranges from 50 to 1000.
[0013] In some embodiments, the current collector is porous carbon or stainless steel foil. Preferably, the porous carbon is at least one of carbon cloth and carbon felt.
[0014] In some embodiments, the method for preparing polyaniline comprises the following steps:
[0015] S1. adding a bridging molecule or a precursor of a bridging molecule to an acidic aqueous solution of aniline to obtain a trimer solution;
[0016] S2, subjecting the trimer solution to an oxidative polymerization reaction to obtain a two-dimensional polyaniline-bridging molecule hybrid;
[0017] S3. Treating the polyaniline-bridging molecule hybrid with an alkaline solution to obtain an intrinsic oxidized amorphous polyaniline having a structure shown in formula (I).
[0018] The bridging molecule is a dibasic weak acid, such as tungstic acid, molybdic acid, terephthalic acid, etc. The molecular precursor of the bridging molecule is the soluble weak base salt listed above, such as ammonium salt. The bridging molecule is preferably tungstic acid, and its precursor is preferably ammonium metatungstate.
[0019] In an embodiment, step S1 has at least one of the following features:
[0020] (1) the acid in the acidic aqueous solution of aniline is sulfuric acid or hydrochloric acid;
[0021] Preferably, the hydrogen ion concentration of the acid solution is 0.2 to 2 mol / L;
[0022] (ii) the concentration of the aniline monomer in the aniline solution is 0.1 to 2 mol / L, and the concentration of the aniline monomer is less than or equal to the hydrogen ion concentration of the acid solution in the aniline solution;
[0023] (iii) the bridging molecule is selected from dibasic weak acids;
[0024] (iv) the molar ratio of the bridging molecule to the aniline monomer is (0.98-1.02):2;
[0025] (V) The molar ratio of the bridging molecule formed by the precursor of the bridging molecule to the aniline monomer is (0.98-1.02):2.
[0026] Step S2 has at least one of the following features:
[0027] (i) an oxidant is added to the trimer solution for oxidative polymerization, wherein the oxidant is selected from at least one of ammonium persulfate, hydrogen peroxide, ferric chloride, and potassium permanganate; preferably, the molar ratio of the oxidant to the aniline monomer is (1.05-2):1;
[0028] (ii) the reaction time of the oxidative polymerization is 6 to 72 hours;
[0029] (iii) The reaction temperature of the oxidative polymerization is -5 to 15°C.
[0030] Step S3 has at least one of the following features:
[0031] (i) the alkaline solution is selected from sodium hydroxide solution or ammonia water, and the molar ratio of the alkali in the alkaline solution to the bridging molecule or the precursor of the bridging molecule is greater than or equal to 2:1;
[0032] (ii) The time of the alkaline solution treatment is 0.5 to 1 hour.
[0033] In a specific embodiment of the present invention, the alkaline solution may be sodium hydroxide or ammonia water. Preferably, the alkaline solution is a sodium hydroxide solution with a concentration of 1 to 2M.
[0034] In a specific embodiment of the present invention, the molar ratio of the alkali to the bridging molecule in the alkaline solution is greater than or equal to 2:1, and is used to react neutrally with the bridging molecule to convert all the bridging molecules in the polyaniline-bridging molecule hybrid into soluble normal salts.
[0035] More preferably, the molar ratio of the alkali to the bridging molecule or the precursor of the bridging molecule in the alkaline solution is greater than 2:1, which is used to react with the bridging molecule to neutralize the bridging molecule, so that all the bridging molecules in the polyaniline-bridging molecule hybrid are converted into soluble normal salts.
[0036] In a specific embodiment of the present invention, the treatment time of the alkaline solution is 0.5 to 1 hour. In a specific example of the present invention, when the alkaline solution is sodium hydroxide, the treatment time of the alkaline solution is 1 hour.
[0037] The alkaline solution treatment is used to destroy the chemical bonds between the polyaniline molecules and the bridging molecules. After the alkaline solution treatment, the bridging molecules are removed, and the two-dimensional crystal structure of the polyaniline-bridging molecule hybrid is dissociated to obtain an intrinsic oxidized amorphous polyaniline without a molecular chain helical structure.
[0038] In some embodiments, the slurry further includes a conductive agent and a binder.
[0039] The mass ratio of the polyaniline, the conductive agent and the binder is (12-18):(2-6):(1-2).
[0040] The content of active material in the positive electrode is less than or equal to 50 mg / cm 2 , preferably 5-25 mg / cm 2 .
[0041] In some embodiments, the conductive agent includes at least one of conductive carbon black, conductive graphite, conductive carbon fiber, carbon nanotube and graphene.
[0042] Preferably, the conductive graphite includes at least one of KS series, SFG series and MX series.
[0043] Preferably, the conductive carbon black includes at least one of SP series, acetylene black and Ketjen black.
[0044] The binder includes at least one of polytetrafluoroethylene and polyvinylidene fluoride.
[0045] On the other hand, the present invention provides a method for preparing a positive electrode of a zinc-iodine battery, comprising the following steps: mixing polyaniline, a conductive agent and a binder according to a certain ratio, adding an organic solvent to form a slurry of active materials; and coating the slurry on a current collector to form a positive electrode.
[0046] Meanwhile, the present invention also provides a zinc-iodine battery, comprising the positive electrode of the zinc-iodine battery or the positive electrode prepared by the method for preparing the positive electrode of the zinc-iodine battery.
[0047] In some of the embodiments, the electrolyte includes a zinc salt aqueous solution, wherein the anions in the zinc salt aqueous solution include iodide ions, the concentration of iodide ions is 0.1-1.5M, and the concentration of zinc ions is 0.5-2.5M.
[0048] Preferably, the anion comprises I - , the anions also include SO 4 2- 、SO 3 F - , CF 3 SO 3 - , BF 4 -Br-I - , Cl - CF 3 COO - , CCl 3 COO - At least one of .
[0049] It should be noted that iodide ions are essential in the electrolyte of the present invention. Iodide ions provide capacity for the battery through redox. In addition to iodine ions, other anions are also included. The role of other anions is to reduce the magnitude of the reduction in electrolyte concentration caused by iodine ions entering the electrode, avoid the reduction of ionic conductivity, and reduce the concentration difference between the electrode and the electrolyte, and avoid the diffusion of ions in the electrode into the electrolyte, resulting in a decrease in coulombic efficiency.
[0050] The technical solution of the present invention has the following advantages:
[0051] The present invention provides a positive electrode of a zinc-iodine battery, the positive electrode comprising a current collector and an active material layer disposed on the current collector, the active material layer being formed by a slurry made of an active material, the active material comprising polyaniline, and the polyaniline having a structure shown in formula (I). The present invention uses polyaniline having an amorphous structure or a low crystallinity structure having a structure shown in formula (I) as an active material to bind iodine and polyiodide ions, because on the one hand, the cation of polyaniline binds iodine or polyiodide anions through electrostatic action, and on the other hand, the space between molecular chains of polyaniline having an amorphous structure or a low crystallinity structure is large, and iodine ions with a small volume can be relatively easily embedded or removed, while polyiodide ions with a large volume will be blocked by the molecular chains, thereby preventing polyiodide ions from diffusing into the electrolyte to cause a decrease in coulombic efficiency, thereby improving specific capacity and coulombic efficiency.
[0052] The positive electrode of a zinc-iodine battery provided by the present invention is applied to a battery, and the iodine ion concentration in the electrolyte is 0.1-1.5 M. The positive electrode of the zinc-iodine battery provided by the present invention can increase the concentration of iodine ions in the electrolyte, and further increase the specific capacity of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0053] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0054] Figure 1 It is a comparison diagram of the XRD diffraction patterns of the polyaniline provided by the present invention and common polyaniline;
[0055] Figure 2 It is a battery charge and discharge curve diagram formed by the positive electrode of the zinc-iodine battery prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0056] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0057] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0058] The polyaniline provided by the present invention is a conductive polymer material with reversible redox (redox reaction is shown in formula (II)). The oxidized polyaniline carries a large amount of positive charges. The polyaniline molecules in the positive electrode material can absorb iodine anions through these positive charges by electrostatic action, thereby binding iodine and preventing iodine from leaking from the electrode into the electrolyte, thereby causing low coulombic efficiency of the battery.
[0059]
[0060] Since the redox potential of polyaniline is slightly lower than that of iodide ions and polyiodide ions, the electrostatic interaction between iodide ions, polyiodide ions and the polyaniline provided by the present invention can be ensured to always exist, thereby avoiding loss from any electrode.
[0061] The redox reaction of the polyaniline positive electrode is as follows (III):
[0062]
[0063] Preparation Example 1
[0064] This preparation example provides a method for preparing amorphous (or low crystallinity) polyaniline, and the specific steps and parameters are as follows:
[0065] 0.02 mol (1.86 g) of aniline was added to 100 mL of 0.2 mol / L sulfuric acid aqueous solution at 15°C, and the mixture was stirred until the aniline and aniline sulfate were completely dissolved to obtain an aniline-sulfuric acid solution with an aniline concentration of 0.2 M; 50 mL of 0.2 mol / L (according to WO 3 The ammonium metatungstate aqueous solution (in terms of weight) is added to the above aniline-sulfuric acid solution to obtain a tungstic acid-aniline-sulfuric acid solution, and the molar ratio of tungstic acid to aniline is 1:2.
[0066] Add 50mL of 0.6mol / L ammonium persulfate solution to tungstate-aniline-sulfuric acid solution, and control the addition time to 1 hour. After the addition is complete, keep stirring, the reaction system temperature is 15°C, and the reaction system temperature is maintained for 6 hours. After the reaction is completed, filter and collect the product, and wash the product with water and ethanol until the filtrate is colorless to obtain a polyaniline-bridged molecule hybrid. Add 100mL of 1mol / L sodium hydroxide aqueous solution to the polyaniline-bridged molecule hybrid, treat for 1h, filter and collect the product to obtain the product, which is amorphous (or low crystallinity) polyaniline.
[0067] The structural formula of the polyaniline prepared in this preparation example is shown in formula (I),
[0068]
[0069] The X-ray powder diffraction patterns of the polyaniline prepared in this preparation example and ordinary polyaniline are shown in Figure 1 ,according to Figure 1 It can be seen that ordinary polyaniline has relatively obvious diffraction peaks at three positions of 2θ of 15°, 20° and 25.5°, indicating that it has a high degree of crystallinity, while the polyaniline provided in this preparation example does not show a significant diffraction peak, indicating that the structure of the intrinsic state polyaniline provided by the present invention is a non-crystalline structure. The polyaniline provided in the present application does not show a significant diffraction peak, which proves that the polyaniline provided in the present application is a non-crystalline structure or a low crystallinity structure. At the same time, the polyaniline provided by the present invention does not have a significant sharp low 2θ angle diffraction peak, and the low crystallinity or non-crystalline structure itself indicates a short-range disordered structure, or it can be said that there is no large number of compact crystal structures, and the molecular chains in these regions are arranged loosely, resulting in polyaniline having a larger molecular chain space, and a larger molecular chain space is more conducive to the entry and escape of ions.
[0070] Preparation Example 2
[0071] This preparation example provides a method for preparing amorphous (or low crystallinity) polyaniline, and the specific steps and parameters are as follows:
[0072] 0.05 mol (4.65 g) of aniline was added to 100 mL of 1 mol / L sulfuric acid aqueous solution at 15°C, and the mixture was stirred until the aniline and aniline sulfate were completely dissolved to obtain an aniline-sulfuric acid solution with an aniline concentration of 0.5 M; 50 mL of 0.5 M (according to WO 3 The ammonium metatungstate solution (in terms of molar weight) is added to the aniline-sulfuric acid solution to obtain a tungstic acid-aniline-sulfuric acid solution, wherein the molar ratio of tungstic acid to aniline is 1:2.
[0073] Add 50mL of 1mol / L ammonium persulfate solution to tungstate-aniline-sulfuric acid solution, and control the dropping time to 1 hour. After the dropwise addition is completed, keep stirring, the reaction system temperature is 15°C, and the reaction system temperature is maintained for 6 hours. After the reaction is completed, filter and collect the product, and wash the product with water and ethanol until the filtrate is colorless to obtain a polyaniline-bridged molecule hybrid. Add 100mL of 1mol / L sodium hydroxide aqueous solution to the polyaniline-bridged molecule hybrid, treat for 1h, filter and collect the product to obtain the product, which is amorphous (or low crystallinity) polyaniline.
[0074] Example 1
[0075] This embodiment provides a method for preparing a positive electrode of a zinc-iodine battery, and the specific steps and parameters are as follows:
[0076] The polyaniline, conductive agent (carbon nanotube CNT), and binder (polyvinylidene fluoride PVDF) powders prepared in Preparation Example 1 were fully mixed and ground in a mass ratio of 8:1:1 to form an active material, and a small amount of isopropanol was added to the active material to form a slurry with a solid content of 25wt%, and the slurry was further ground until it had good fluidity. The slurry was applied to a current collector (stainless steel foil) by doctor blade coating to form an active material layer, and vacuum dried at 80°C. The thickness of the active material layer on the current collector was about 30μm.
[0077] The content of active material on the positive electrode prepared in this example is 5 mg / cm 2 .
[0078] The positive electrode, separator and zinc foil are sequentially loaded into a button battery of specification 2032, and an electrolyte (200 μL) is added thereto, wherein the components of the electrolyte are zinc iodide (0.5 M), zinc sulfate (1 M), tetraethylammonium bromide (0.15 wt %), the solvent is deionized water, and the separator is glass fiber, to obtain a battery.
[0079] The battery capacity test adopts the constant current charge and discharge method, taking the mass of the battery positive electrode material as a reference, and adopts three different current densities of 1A / g, 2A / g and 5A / g for constant current charge and discharge test, and the charge and discharge voltage range is 0.6~1.5V. The charge and discharge test results are shown in Table 1. The battery charge and discharge curve formed by the positive electrode prepared in this embodiment is shown in Figure 2 .
[0080] Example 2
[0081] This embodiment provides a method for preparing a positive electrode of a zinc-iodine battery. The specific steps and parameters are the same as those in Embodiment 1, except that the thickness of the active material layer on the current collector is 55 μm.
[0082] The content of active material on the positive electrode prepared in this example is 10 mg / cm2 .
[0083] The battery manufacturing method and testing method are the same as those in Example 1.
[0084] Example 3
[0085] This embodiment provides a method for preparing a positive electrode of a zinc-iodine battery. The specific steps and parameters are the same as those in Embodiment 1, except that the thickness of the active material layer on the current collector is about 125 μm.
[0086] The content of active material on the positive electrode prepared in this example is 25 mg / cm 2 .
[0087] The battery manufacturing method and testing method are the same as those in Example 1.
[0088] Example 4
[0089] This embodiment provides a method for preparing a positive electrode. The specific steps and parameters are the same as those in Embodiment 1, except that the thickness of the active material layer on the current collector is about 230 μm.
[0090] The content of active material on the positive electrode prepared in this example is 50 mg / cm 2 .
[0091] The battery manufacturing method and testing method are the same as those in Example 1.
[0092] Example 5
[0093] This embodiment provides a method for preparing a positive electrode, and the specific steps and parameters are as follows:
[0094] The polyaniline, conductive agent (conductive graphite), and binder (tetrafluoroethylene) powders prepared in Preparation Example 1 were fully mixed and ground in a mass ratio of 6:3:1 to form an active material, a small amount of isopropanol was added to the active material to form a slurry with a solid content of 15wt%, and the slurry was further ground until it had good fluidity. The slurry was applied on the current collector (carbon cloth) by doctor blade coating to form an active material layer, and vacuum dried at 80°C.
[0095] The content of active material on the positive electrode prepared in this embodiment is about 5 mg / cm 2 .
[0096] The battery manufacturing method and testing method are the same as those in Example 1.
[0097] Example 6
[0098] This embodiment provides a method for preparing a positive electrode, and the specific steps and parameters are as follows:
[0099] The polyaniline, conductive agent (ketjen black), and binder (tetrafluoroethylene) powders prepared in Preparation Example 1 were fully mixed and ground in a mass ratio of 75:20:5 to form an active material, a small amount of isopropanol was added to the active material to form a slurry with a solid content of 30wt%, and the slurry was further ground until it had good fluidity. The slurry was applied on the current collector (carbon felt) by doctor blade coating to form an active material layer, and vacuum dried at 80°C.
[0100] The content of active material on the positive electrode prepared in this example is 15 mg / cm 2 .
[0101] The battery manufacturing method and testing method are the same as those in Example 1.
[0102] Example 7
[0103] The electrode and battery manufacturing and testing methods are the same as those in Example 1, except that the concentration of zinc iodide in the electrolyte is 0.1 M.
[0104] Example 8
[0105] The electrode and battery manufacturing and testing methods are the same as those in Example 1, except that the concentration of zinc iodide in the electrolyte is 1.5 M.
[0106] Example 9
[0107] This embodiment provides a method for preparing a positive electrode, and the specific steps and parameters are as follows:
[0108] The polyaniline, conductive agent (graphene), and binder (polytetrafluoroethylene) powders prepared in Preparation Example 1 were fully mixed and ground in a mass ratio of 9:1:1 to form an active material, and a small amount of isopropanol was added to the active material to form a slurry with a solid content of 25wt%, and the slurry was further ground until it had good fluidity. The slurry was applied to a current collector (stainless steel foil) by doctor blade coating to form an active material layer, and vacuum dried at 80°C. The thickness of the active material layer on the current collector was about 30μm.
[0109] The content of active material on the positive electrode prepared in this example is 5 mg / cm 2 .
[0110] The preparation method of the battery refers to the preparation method of the battery in Example 1.
[0111] Example 10
[0112] This embodiment provides a method for preparing a positive electrode, and the specific steps and parameters are as follows:
[0113] The polyaniline, conductive agent (acetylene black), and binder (polyvinylidene fluoride PVDF) powders prepared in Preparation Example 1 were fully mixed and ground in a mass ratio of 8:1:1 to form an active material, and a small amount of isopropanol was added to the active material to form a slurry with a solid content of 25wt%, and the slurry was further ground until it had good fluidity. The slurry was applied to the current collector (stainless steel foil) by doctor blade coating to form an active material layer, and vacuum dried at 90°C. The thickness of the active material layer on the current collector was about 30μm.
[0114] The content of active material on the positive electrode prepared in this example is 5 mg / cm 2 .
[0115] The preparation method of the battery refers to the preparation method of the battery in Example 1.
[0116] Comparative Example 1
[0117] This comparative example provides a method for preparing a positive electrode. The specific steps and parameters are the same as those in Example 1, except that an equal mass of activated carbon is used to replace the polyaniline in Example 1, and the positive electrode loading obtained is 10 mg / cm 2 .
[0118] The battery manufacturing method and testing method are the same as those in Example 1.
[0119] Comparative Example 2
[0120] This comparative example provides a method for preparing a positive electrode. The specific steps and parameters are the same as those in Example 1, except that ordinary polyaniline of the same mass is used to replace the polyaniline in Example 1.
[0121] The preparation method of ordinary polyaniline, the specific steps and parameters are as follows: add 1.86 grams of aniline to 100 mL of 0.2 mol / L sulfuric acid aqueous solution at 15°C, keep stirring, stir until aniline and aniline sulfate are completely dissolved, and obtain aniline-sulfuric acid solution; add 50 mL of 0.6 mol / L ammonium persulfate solution to the aniline-sulfuric acid solution, and control the drop time to 1 hour. After the dropwise addition is completed, keep stirring, the temperature of the reaction system is 15°C, and the temperature of the reaction system is maintained for 6 hours. After the reaction is completed, filter and collect the product, and wash the product with water and ethanol until the filtrate is colorless to obtain doped polyaniline. Add 100 mL of 1 mol / L sodium hydroxide aqueous solution to the doped polyaniline, treat for 1 hour, filter and collect the product, and obtain the product, which is ordinary polyaniline.
[0122] The battery manufacturing method and testing method are the same as those in Example 1.
[0123] Result Analysis: The specific capacity and coulombic efficiency of the batteries formed in Examples 1-8 and Comparative Examples 1-2 at current densities of 1 A / g, 2 A / g, and 5 A / g were measured respectively. The results are shown in Table 1.
[0124] Table 1 Battery performance test results
[0125]
[0126] According to the data in Table 1, compared with Comparative Example 1 using activated carbon and Comparative Example 2 using ordinary polyaniline as the main component of the positive electrode active material, the positive electrode prepared with polyaniline of a specific structure as the active material provided by the embodiment of the present invention can significantly improve the specific capacity and coulombic efficiency, and with the increase of current density, the coulombic efficiency is also significantly improved.
[0127] At the same time, the content of active material on the positive electrode of the embodiment of the present invention is 5-25 mg / cm 2 When the coulombic efficiency and specific capacity are improved, it performs better.
[0128] The positive electrode provided by the present invention can form a battery with an electrolyte having a high iodine ion concentration, and has a high specific capacity.
[0129] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. A positive electrode of a zinc-iodine battery, characterized in that: The positive electrode comprises a current collector and an active material layer disposed on the current collector. The active material layer is formed of a slurry made of an active material, wherein the active material includes polyaniline, The polyaniline has a structure shown in formula (I), 2. The positive electrode of the zinc-iodine battery according to claim 1, characterized in that: The method for preparing polyaniline having the structure shown in formula (I) comprises the following steps: S1. adding a bridging molecule or a precursor of a bridging molecule to an aniline solution to obtain a trimer solution; S2, subjecting the trimer solution to an oxidative polymerization reaction to obtain a polyaniline-bridging molecule hybrid; S3. Treating the polyaniline-bridging molecule hybrid with an alkaline solution to obtain an intrinsic oxidized amorphous polyaniline having a structure shown in formula (I).
3. The positive electrode of the zinc-iodine battery according to claim 2, characterized in that: Step S1 has at least one of the following features: (i) the aniline solution further comprises an acid solution, the acid solution is selected from a medium-strong acid solution or a strong acid solution, and preferably, the hydrogen ion concentration of the acid solution is 0.2 to 2 mol / L; (ii) the concentration of the aniline monomer in the aniline solution is 0.1 to 2 mol / L, and the concentration of the aniline monomer is less than or equal to the hydrogen ion concentration of the acid solution in the aniline solution; (iii) the bridging molecule is selected from dibasic weak acids; (iv) the molar ratio of the bridging molecule to the aniline monomer is (0.98-1.02):2; (V) The molar ratio of the bridging molecule formed by the precursor of the bridging molecule to the aniline monomer is (0.98-1.02):
2.
4. The positive electrode of the zinc-iodine battery according to claim 3, characterized in that: The slurry also includes a conductive agent and a binder.
5. The positive electrode of the zinc-iodine battery according to claim 4, characterized in that: The mass ratio of the polyaniline, the conductive agent and the binder is (12-18):(2-6):(1-2).
6. The positive electrode of the zinc-iodine battery according to claim 5, characterized in that: The content of active material in the positive electrode is less than or equal to 50 mg / cm 2 , preferably 5-25 mg / cm 2 and / or, The conductive agent includes at least one of conductive carbon black, conductive graphite, conductive carbon fiber, carbon nanotube and graphene.
7. The positive electrode of the zinc-iodine battery according to claim 6, characterized in that: The conductive graphite includes at least one of KS series, SFG series and MX series; and / or, The conductive carbon black comprises at least one of SP series, acetylene black and Ketjen black; and / or, The binder includes at least one of polytetrafluoroethylene and polyvinylidene fluoride.
8. A method for preparing a positive electrode of a zinc-iodine battery according to any one of claims 1 to 7, characterized in that: The following steps are included: The polyaniline, the conductive agent and the binder are mixed in a certain ratio, and an organic solvent is added to form a slurry of the active material; The slurry is coated onto a current collector to form a positive electrode.
9. A zinc-iodine battery, characterized in that: The positive electrode comprises the positive electrode of the zinc-iodine battery according to any one of claims 1 to 7 or the positive electrode prepared by the method for preparing the positive electrode of the zinc-iodine battery according to claim 8.
10. The zinc-iodine battery according to claim 9, characterized in that: The electrolyte includes a zinc salt aqueous solution, wherein the anions in the zinc salt aqueous solution include iodide ions, the concentration of the iodide ions is 0.1-1.5M, and the concentration of the zinc ions is 0.5-2.5M.
Citation Information
Patent Citations
Preparation method of high-performance zinc-polyaniline secondary battery
CN106935916A
Aqueous zinc-iodine secondary battery positive electrode material and positive electrode thereof, and aqueous zinc-iodine secondary battery
CN113725414A
High-performance chargeable-dischargeable aqueous zinc-iodine battery and preparation method thereof
CN113782710A
Water-based high-energy-density zinc-iodine electrochromic battery
CN116190543A
Oxidized amorphous polyaniline as well as preparation method and application thereof
CN117586500A